2021
DOI: 10.1371/journal.pone.0258284
|View full text |Cite
|
Sign up to set email alerts
|

Low bone turnover is associated with plain X-ray vascular calcification in predialysis patients

Abstract: Background Vascular calcification (VC) is a common finding in chronic kidney disease (CKD) patients and predicts subsequent cardiovascular morbidity and mortality in this population. Vascular calcification is linked to disordered mineral metabolism and has been associated with bone histomorphometry changes in CKD. However, data on predialysis patients is scarce. Methods A cross-sectional study was conducted on a cohort of 56 CKD patients not yet on dialysis, who underwent a transiliac bone biopsy for histomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…This is supported by two recent studies in stage 3 and 4 CKD, which identified a link between high sclerostin levels and low rates of bone turnover with a corresponding increase in VC [90,150]. The independent association between VC and the rate of bone formation highlights evidence of a key interplay between bone and the cardiovascular system in patients with CKD [90].…”
Section: Sclerostinsupporting
confidence: 60%
See 2 more Smart Citations
“…This is supported by two recent studies in stage 3 and 4 CKD, which identified a link between high sclerostin levels and low rates of bone turnover with a corresponding increase in VC [90,150]. The independent association between VC and the rate of bone formation highlights evidence of a key interplay between bone and the cardiovascular system in patients with CKD [90].…”
Section: Sclerostinsupporting
confidence: 60%
“…The association with VC may be important, as outlined in a further study demonstrating that serum sclerostin levels correspond with an increased risk of both fatal and non-fatal cardiovascular events in a non-dialysis CKD population, even after multiple statistical adjustments [156]. This is supported by two recent studies in stage 3 and 4 CKD, which identified a link between high sclerostin levels and low rates of bone turnover with a corresponding increase in VC [90,150]. The independent association between VC and the rate of bone formation highlights evidence of a key interplay between bone and the cardiovascular system in patients with CKD [90].…”
Section: Sclerostinmentioning
confidence: 65%
See 1 more Smart Citation
“…Elevated sclerostin levels correlate with cardiovascular events, both fatal and non-fatal [ 144 ]. This association underscores the interplay between altered bone turnover and the development of vascular calcification [ 145 ].…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…The small sample size ( n = 41), the use of a semiquantitative method to evaluate VC (Kaupilla score), and the relatively low prevalence of VC (24.3%) may, at least partially, explain this unexpected result. In pre-dialysis patients, low bone-formation rate has been independently associated with VC, evaluated either by CT or by plain X-ray [ 4 , 87 ].…”
Section: Adb As a Risk Factor For Vascular Calcificationmentioning
confidence: 99%